Avian haematology and biochemistry 1. Haematology. Issue 10 (13th November 2014) - Sabater, Mikel; Forbes, Neil
Abstract : The class Aves contains more than 9000 species of birds classified in 199 families. While few species‐specific haematological characteristics have been described, there are clear intra‐class variations and differences from vertebrates. This article, the first of a two‐part series on avian haematology and biochemistry, concentrates on haematology. It includes guidance on how to collect blood samples, how to assess the sample and information on the haematological disorders most commonly found in birds.